1998
DOI: 10.1002/ana.410440115
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal molecular mimicry in immune‐mediated neurologic disease

Abstract: Molecular mimicry is implicated in the pathogenesis of autoimmune diseases such as diabetes mellitus, rheumatoid arthritis, and multiple sclerosis (MS). Cellular and antibody-mediated immune responses to shared viral-host antigens have been associated with the development of disease in these patients. Patients infected with human T-lymphotropic virus type I (HTLV-I) develop HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP), an immune-mediated disorder of the central nervous system (CNS) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 38 publications
3
43
0
2
Order By: Relevance
“…In addition to its deleterious effects on neural cells, sCD100 could participate in the autoimmune response within the brain of patients suffering with neuroinflammatory demyelination (21,51). In fact, the two murine immune semaphorins, CD100 and SEMA-4A, are expressed constitutively in T cells and function as soluble ligands to CD72 and Tim2, respectively, to regulate the humoral and cellular immune response (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its deleterious effects on neural cells, sCD100 could participate in the autoimmune response within the brain of patients suffering with neuroinflammatory demyelination (21,51). In fact, the two murine immune semaphorins, CD100 and SEMA-4A, are expressed constitutively in T cells and function as soluble ligands to CD72 and Tim2, respectively, to regulate the humoral and cellular immune response (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…CTLs and activated macrophages into the CNS has been postulated to play a critical role in the pathogenesis of HAM/ TSP (Levin et al, 1997a(Levin et al, , 1998. With respect to bone marrow (BM) from individuals with HAM/TSP and likely a subset of asymptomatic carriers, previous studies utilizing PCR-in situ hybridization analyses have demonstrated that a vast majority of cells within the BM are positive for HTLV-I proviral DNA, but negative for viral RNA expression, suggesting the presence of an extensive latent infection (Levin et al, 1997b).…”
Section: Overview Of the Pathogenic Processmentioning
confidence: 99%
“…Additional damage may also be caused by the recognition and disruption of uninfected neurons by crossreactive anti-HTLV-I antibodies (Levin et al, 1998). CNS dysfunction may also be caused directly or indirectly by HTLV-I-induced dysregulation of astrocytic, macrophage, microglial, or neuronal function mediated by the multifunctional Tax protein.…”
Section: Transition From Normal Immune Surveillance To Neuroinflammationmentioning
confidence: 99%
“…Data indicate that IgG has a significant role in the pathogenesis of these diseases 7,8,21 . In HAM/TSP, patients are infected with HTLV-1, which is tropic for CD4 + T-lymphocytes 7 .…”
mentioning
confidence: 99%